2012
DOI: 10.1002/jobm.201100520
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phosphorus and pH on the fungicidal potential of Anabaena strains

Abstract: The genus Anabaena is known to be a rich source of bioactive metabolites, but the biocontrol potential of this genus, mediated through hydrolytic enzymes is less investigated. In our investigation, five Anabaena strains – A. laxa RPAN8, A. iyengarii RPAN9, A. variabilis RPAN59 and A. oscillarioides RPAN69 (with A. variabilis RPAN16 serving as negative control) were evaluated in time course studies involving incubation under three levels of phosphorus and pH conditions. Total chlorophyll, proteins, chitosanase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…; Chaudhary et al . ). However, in the field, pH is affected by the uptake of carbon dioxide during cyanobacterial photosynthesis, which increases the pH surrounding the cyanobacterial cell (Planavsky et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Chaudhary et al . ). However, in the field, pH is affected by the uptake of carbon dioxide during cyanobacterial photosynthesis, which increases the pH surrounding the cyanobacterial cell (Planavsky et al .…”
Section: Discussionmentioning
confidence: 97%
“…At pH values of 5 and 9, the synthesis of the metabolite undergoes a reduction of about 98.35 and 63.8%, respectively [ 306 ]. Chaudhary, Prasanna, and Bhatnagar (2012) [ 317 ] demonstrated that the growth of Anabaena strains differ under distinct pH conditions, thus resulting in significant changes in the fungicidal potential of the cell-free filtrate obtained from these cyanobacteria. Using P. debaryanum and F. oxysporum during the experiment, it was noted that such consequences vary depending on the target microorganism utilized.…”
Section: Regulationmentioning
confidence: 99%
“…Using P. debaryanum and F. oxysporum during the experiment, it was noted that such consequences vary depending on the target microorganism utilized. For example, although a pH of 5.5 provides the best conditions for the acquisition of antimicrobial metabolites from the RP69 strain that works against P. debaryanum , the same pH has no elicitor effect on the antagonistic activity that works against F. oxysporum , compared with the other tested pH values (7.5 and 9.5) [ 317 ]. On some occasions, the optimum pH for cyanobacterial growth offered the most favorable environment for the synthesis of the biocide compounds, S. maxima and S. ocellatum ; indeed, their best growth and inhibitory compound production occurred between the pH values of 8.0–8.5 [ 299 , 318 ].…”
Section: Regulationmentioning
confidence: 99%
“…Estos valores permanecieron en el rango de 7-10 sin requerir ser controlados mediante la adición de sustancias amortiguadoras. Dicho rango resulta adecuado para el crecimiento de cada uno de los organismos presentes en el CM como proteobacterias, cianobacterias, flavobacterias, microalgas y diatomeas (Eroğlu et al 2008, Roubeix y Lancelot 2008, Chaudhary et al 2012, Hadas et al 2013, Silaban et al 2013, Hernández 2015.…”
Section: Estudiaron La Producción Deunclassified